2012
DOI: 10.1111/j.1349-7006.2012.02259.x
|View full text |Cite
|
Sign up to set email alerts
|

Chemokine CC motif receptor 5 and CC motif ligand 5 promote cancer cell migration under hypoxia

Abstract: The chemokine CC motif receptor 5 (CCR5) and its ligands have been reported to be associated with cancer progression and metastasis. Although recent researches have demonstrated a fundamental role of hypoxia in cancer, the effect of hypoxia on the expression and function of CCR5 and its ligands in cancer cells is unknown. Here, we investigated the status of CCR5 and its ligands in cancer cells under hypoxic conditions. Quantitative polymerase chain reaction, western blotting and immunofluorescence staining sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
75
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(77 citation statements)
references
References 29 publications
1
75
0
1
Order By: Relevance
“…The study reported that mice expressing CCR5 exhibited enhanced local tumor growth and an impaired response to vaccine therapy compared with CCR5-knockout mice. Lin et al (29) reported that CCR5 and CCL5 were highly expressed in breast cancer lymph node metastasis, and that CCR5-CCL5 interaction promotes cancer cell migration under hypoxic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The study reported that mice expressing CCR5 exhibited enhanced local tumor growth and an impaired response to vaccine therapy compared with CCR5-knockout mice. Lin et al (29) reported that CCR5 and CCL5 were highly expressed in breast cancer lymph node metastasis, and that CCR5-CCL5 interaction promotes cancer cell migration under hypoxic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…3 Overexpression of CCR5 increases cell migration, and knockdown of CCR5 attenuates hypoxia-mediated cell migration. 4 A mutant allele of CCR5, CCR5del32, is frequently found in populations of northern European origin and encodes a nonfunctional truncated protein that is not transported to the cell surface. 5…”
mentioning
confidence: 99%
“…3 Overexpression of CCR5 increases cell migration, and knockdown of CCR5 attenuates hypoxia-mediated cell migration. 4 A mutant allele of CCR5, CCR5del32, is frequently found in populations of northern European origin and encodes a nonfunctional truncated protein that is not transported to the cell surface. 5 The 32-bp deletion results in a frameshift, whereby the CCR5delta32 allele encodes for a protein with a transdominant negative effect on the wildtype protein.…”
mentioning
confidence: 99%
“…The results revealed that although ER stress upregulated intracellular CCL5 expression, it inhibited CCL5 secretion of MCF-7 cells. According to studies of Wang et al (10) and Lin et al (28), CCL5 promotes tumour cell motility and migration by interacting with a specific receptor chemokine C-C motif receptor 5 (CCR5). Thus, we assume that it is the extracellular CCL5 in the microenvironment of tumour cells that actually stimulates the migration, while the intracellular expression level of CCL5 does not affect the migration ability of cancer cells directly.…”
Section: Discussionmentioning
confidence: 99%